Defining Internationalization Strategies of Indonesian Universities through Educational Investment Preferences - Inaya Sari Melati; Yulhendri Yulhendri; Hana Netti Purasani (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
The internationalization program for higher education is a promising investment with a valuable return. However, it needs a huge budget. This research aims to analyze investment preferences of 13 internationalization program dimensions in Indonesian universities which aggressively encourage themselves to be a world-class university in the future. The novelty in this research is the usage of investment preference index in determining investment priorities in universities instead of common business entities. The quantitative approach was used by calculating the investment preference index. The research instrument used questionnaire with Likert Scale. Respondents were 190 people including students and lecturers. Based on the investment preference index, the number of international students in undergraduate program had to be the first focus in allocating the money for educational investment, followed by the number of international students in postgraduate program and student exchange program. Meanwhile, international links became the least aspect in educational investment preferences.